The costs and benefits of early sport specialization: A critical review of literature - Waldron, S.; DeFreese, J. D.; Register-Mihalik, J.; Pietrosimone, B.; Barczak, N. (Quest, 2020)
There is a growing trend toward specialization in American youth sport, evident in the number of elite youth competitions and position statements from major medical organizations. Despite growing interest on this topic for kinesiology professionals within higher education, there is a dearth in research regarding the relationship between specialization and athlete health outcomes, especially psychosocial outcomes. This critical review describes specialization theory and the limited extant research on the costs and benefits of single-sport specialization. Topics include: (a) the proposed benefits of specialization from the performance perspective; (b) early specialization and alternative sport participation pathways; (c) the posited psychosocial and physical health risks of sport specialization; (d) ethical concerns; and (e) methodological issues and recommendations for future research. Deeper understanding of the costs and benefits of sport specialization has significant practical implications for youth athletes` performance and well-being and for other relevant stakeholders in the youth sport system.